Echinococcus granulosus antigen 5 is closely related to proteases of the trypsin family. - Lorenzo, Carmen (2003)
Antigen 5 (Ag5) is a dominant secreted component of the larval stage of Echinococcus granulosus, and is highly immunogenic in human infections. Although the diagnostic value of Ag5 has been thoroughly evaluated, there has been little progress in its molecular characterization and the understanding of its biological role. In the present study, the Ag5 gene was cloned by reverse transcription-PCR on the basis of the amino acid sequences of tryptic fragments. The nucleotide sequence indicates that Ag5 is synthesized as a single polypeptide chain that is afterwards processed into single disulphide-bridged 22 and 38 kDa subunits. Whereas the 22 kDa component contains a highly conserved glycosaminoglycan-binding motif that may help to confine Ag5 in the host tissue surrounding the parasite, the 38 kDa subunit is closely related to serine proteases of the trypsin family. The sequences in the vicinity of the active-site histidine, aspartic acid and serine residues, and critical cysteine residues involved in disulphide formation, are well conserved, but the catalytic serine residue is replaced by threonine. Since there are no significant chemical differences between the O gamma atoms of these residues, we performed a series of enzymic assays to find out whether Ag5 is a catalytic molecule. Neither proteolytic activity nor binding to protease inhibitors could be detected using the native purified antigen. Thus it may be possible that Ag5 possesses a highly specific physiological substrate or, more likely, that trypsin-like folding has been recruited to fulfil novel functions.